Comparing different pneumoperitoneum (12 vs. 15 mmHg) pressures with cytokine analysis to evaluate clinical outcomes in patients undergoing robotic‐assisted laparoscopic radical cystectomy and intracorporeal robotic urinary diversion - Nikhil Vasdev; Naomi Martin; Amon B. Hackney; John Piedad; Alexander Hampson; Gowrie‐Mohan Shan; Venkat Prasad; Michael Chilvers; Martin Ebon; Philip Smith; Gary Tegan; Karel Decaestecker; et al. (BJUI Compass, 2023)
Abstract Background Robotic cystectomy is the mainstay surgical intervention for treatment‐refractory nonmuscle‐invasive and muscle‐invasive bladder cancer. However, paralytic ileus may complicate the postoperative recovery and may be a consequence of an inflammatory response associated with transient gut ischaemia. We have therefore investigated clinical, operative and inflammatory biomarker associations between paralytic ileus in the context of robotic cystectomy and intracorporeal ileal conduit urinary diversion. Methods Prospective consective patients referred for robotic cystectomy were consented and included in the study, while patients >75 years old and converted to open procedure were excluded. The pneumoperitoneum pressure (PP) for carbon dioxide insufflation required to perform the procedure efficiently and safely was recorded (12 or 15 mmHg). We also recorded the postoperative days patients passed flatus and stools, whether they developed ileus, as well as other standard clinical and demographic data. The expression of select proinflammatory and anti‐inflammatory cytokines was determined by multiplex analysis using a cytometric bead array with changes in profiles correlated with the pressures applied and with the existence of an ileus. Results Twenty‐seven patients were recruited, but only 20 were used in the study with 10 patients in each PP group. Seven patients were excluded all of whom had an extracorporeal ileal conduit formation. There were differences in the 40‐min shorter operative time and 1 day shorter length of stay, as well as passing flatus 1 day and stools 1.5 days earlier in the 12 mmHg compared with the 15 mmHg group. More patients had ileus in the 15 mmHg group vs 12 mmHg group (30% vs. 10.0%). These were not statistically significant. Similarly, there were no statistical differences in the expression of proinflammatory cytokines at the two different pressures or between patient groups, but there were outliers, with the median indicating nonsymmetrical distribution. By comparison, anti‐inflammatory cytokines showed some significant differences between groups, with IL‐6 and IL‐10 showing elevated levels postsurgery. No statistical difference was observed between pressures or the existence of an ileus, but the maximum levels of IL‐6 and IL‐10 detected in some patients reflect a pressure difference. Conclusions The initial findings of this novel scientific study indicated a higher risk of paralytic ileus postrobotic cystectomy and robotic intracorporeal urinary diversion when a higher pressure of 15 mmHg is used compared with 12 mmHg. Although further studies are required to establish the linkage between cytokine profile expression, pressure and ileus, our initial data reinforces the advantages of lower pressure robotic cystectomy and intracorporeal urinary diversion in patient outcomes.